2023
DOI: 10.11591/ijere.v12i2.24422
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of academic supervision to vocational students’ learning readiness

Abstract: The learning process in vocational schools has different characteristics compared to that of the non-vocational. Students’ readiness is one significant variable in determining students’ learning success. Hence, identifying the antecedent of the variable is necessary. The research aimed to measure the contribution of academic supervision through teachers' professional and pedagogic competence and its impact on vocational school students’ learning readiness. The quantitative research employed ex-post facto desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…This fact illustrates that the Principal's academic supervision has not been able to achieve the objectives optimally. This statement is supported by the study results (Pusporini et al, 2020;Rahabav, 2016;Suyatno et al, 2023).…”
Section: Indirect Effectssupporting
confidence: 60%
See 1 more Smart Citation
“…This fact illustrates that the Principal's academic supervision has not been able to achieve the objectives optimally. This statement is supported by the study results (Pusporini et al, 2020;Rahabav, 2016;Suyatno et al, 2023).…”
Section: Indirect Effectssupporting
confidence: 60%
“…Academic supervision is a process designed and implemented by the Principal to help improve the quality of implementing teacher duties in schools. Academic supervision allows them to improve the quality of service to students and school stakeholders (Farida & Kenedi, 2021;Istiningsih et al, 2020;Noor et al, 2020;Suyatno et al, 2023). Academic supervision is an effort made by the Principal to ensure the achievement of the school's vision, mission, goals, and management (Al-Saree et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted by (Suyatno et al, 2023) delineates a discernible positive correlation between pedagogic competence and learning readiness, while discerning an absence of statistically significant impact stemming from professional competence on the latter. Moreover, the study elucidates the dual facilitative role of academic supervision in enhancing both pedagogic and professional competencies.…”
Section: Introductionmentioning
confidence: 96%
“…The principal's leadership exerts a substantial and beneficial impact on teacher conduct. Prior research on academic supervision has demonstrated that when school leaders engage in academic supervision, it enhances teacher performance and fosters teacher competence within an educational institution (Nasution et al, 2023;Noor et al, 2020;Saihu, 2020;Suyatno et al, 2023). Prior research has shown that teachers' performance is significantly influenced by principal leadership and teacher motivation in completing tasks (Firlianza & Suhardi, 2024;Mukhtar et al, 2024).…”
Section: Introductionmentioning
confidence: 99%